Información y Documentación: fundamentación teórica y coyuntura académica - Moscoso Castro, Purificación (Revista General de Información y Documentación, 2010)
The aim of this paper is to identify the hallmarks of the Information Science in XXI century, which are part of the scientific and social context that led to the emergence of the Information Science. The theoretical analysis is based on the concept of information and electronic document. The multiple uses and meanings of information are taken into consideration, as well as the relationships with concepts that are considered inseparable in the field of this discipline: knowledge and technology, need and use, market good and the common good. Then, the features of the electronic document that led to the redefinition of the concept of document are analized, as well as the main consequences that the spread of the electronic document has had on the discipline.